Imaging α-synuclein pathologies in animal models and patients with Parkinson's and related diseases - Endo, Hironobu; Ono, Maiko; Takado, Yuhei; Matsuoka, Kiwamu; Takahashi, Manami; Tagai, Kenji; Kataoka, Yuko; Hirata, Kosei; Takahata, Keisuke; Seki, Chie; Kokubo, Naomi; Fujinaga, Masayuki; et al. (Neuron (Cambridge, Mass.), 2024)
Deposition of α-synuclein fibrils is implicated in Parkinson's disease (PD) and dementia with Lewy bodies (DLB), while in vivo detection of α-synuclein pathologies in these illnesses has been challenging. Here, we have developed a small-molecule ligand, C05-05, for visualizing α-synuclein deposits in the brains of living subjects. In vivo optical and positron emission tomography (PET) imaging of mouse and marmoset models demonstrated that C05-05 captured a dynamic propagation of fibrillogenesis along neural pathways, followed by disruptions of these structures. High-affinity binding of F-C05-05 to α-synuclein aggregates in human brain tissues was also proven by in vitro assays. Notably, PET-detectable F-C05-05 signals were intensified in the midbrains of PD and DLB patients as compared with healthy controls, providing the first demonstration of visualizing α-synuclein pathologies in these illnesses. Collectively, we propose a new imaging technology offering neuropathology-based translational assessments of PD and allied disorders toward diagnostic and therapeutic research and development.